Primary Dural Closure for Retrosigmoid Approaches - Venable, Garrett T.; Roberts, Mallory L.; Lee, Ryan P.; Michael, L. Madison, II (Journal of Neurological Surgery Part B: Skull Base, 2018)
Object Primary closure of posterior fossa dura can be challenging, and postoperative cerebrospinal fluid (CSF) leaks continue to represent a common complication of the retrosigmoid approach. We describe a simple technique to allow for primary closure of the dura following retrosigmoid approaches. The incidence of CSF leaks using this method is reported.Methods A retrospective chart review was conducted on all cases of retrosigmoid craniotomies performed by the senior surgeon from February 2009 to February 2015. The primary outcome was development of postoperative CSF leak or pseudomeningocele. Length of stay, lesion type, and other surgical complications were also reported.Results Eighty-six patients underwent a retrosigmoid craniotomy during the study period. The most common indications for retrosigmoid craniotomy were microvascular decompression (58%) and tumor resection (36%). No allo- or autografts to repair the dural defect were needed, and no lumbar drains were used. No patients developed CSF otorrhea, rhinorrhea, or incisional leak postoperatively.Conclusion Primary dural closure is possible in retrosigmoid approaches without the use of allo- or autografts and may prevent postoperative CSF leaks when combined with other posterior fossa closure techniques. Careful attention to the handling of the dural flap is necessary to achieve this.
Keywords: retrosigmoid craniotomy; retrosigmoid approach; primary dural closure; CSF leak